A Produtora Brasil Paralelo e o consumo de militância política no capitalismo digital - Belo, Fernando Souza (2023)
This work examines how production company Brasil Paralelo exploits the scenario of cultural and ideological war in Brazil today, making viable a business model based on the production and distribution of content that mobilizes the new right’s ideals and a communication strategy that frames the consumption of its products as an act of political militancy. We find in the inherent conditions of digital capitalism the determining elements that allowed for the emergence and success of the company. To that end, we will discuss the different aspects of society’s platformization process, such as Affective Economics (ANDREJEVIC, 2001), the Attention Economy (BUENO, 2017), group polarization (RIVERA, 2020; SUNSTEIN, 2001) and the deterioration of the public space of discussion (MISKOLCI, 2021; MENDONÇA; AGGIO, 2021). We also discuss how Brasil Paralelo offers its audience the opportunity to forge a communicable political identity and worldview in a process that is typical of Consumption Culture (CANCLINI, 1995; FONTENELLE, 2017). In the course of this work, we will present some examples of documentaries, articles, interview programs and e-books distributed by the company and promotional videos and instances of its communication on social media, pointing out occurrences of the mobilization of the new right’s ideals and of political summoning for consumption that typify the instrumentalization of sociopolitical tensions for profit. At the end of this research, we diagnose the commodification of political militancy and, from the juxtaposition of the theories and the empirical elements that are part of this research, we point to possible consequences to the public sphere and, ultimately, to the democratic system as a whole.